The Distribution Pattern and Spatial Morphological Characteristics of Military Settlements Along the Ming Great Wall in the Hexi Corridor Region - Baolong Jiang; Yuhao Huang; Yile Chen; Jie Lu; Tianfu Yang (Buildings)
Military settlements along the Ming Great Wall are typical representatives of the construction of the ancient Chinese military defense system. The location of the military fortification is complex, and the settlements are scattered and affected by multiple factors. The academic community lacks systematic research on the military settlements along the Ming Great Wall. Existing studies focus on local protection, especially the regional connectivity and overall defense mechanism of the military settlements in the Hexi Corridor. This study incorporates the distribution, morphology, and function of the military settlements in the Hexi Corridor into a unified analytical framework to explore the coordinated defense mechanism under the spatial attributes of the military settlements. Additionally, this study looks at the distribution pattern of 173 local military settlements using tools such as the kernel density index, the Moran index, and the buffer zone. It also conducts statistical analyses of 85 existing settlements to determine their scale and morphological index and uses 18 typical settlements as examples to investigate their spatial morphology using space syntax. This study’s findings indicate that (1) military settlements are spread out in a straight line, which is affected by many things such as terrain, water systems, oasis, and the Great Wall; (2) military facilities and environmental factors are strongly connected and linked in space; (3) military settlements have obvious cluster characteristics, and most are relatively regular quadrilaterals; and (4) the organizational logic of the internal space form is consistent. The main blocks are highly accessible, and the overall space is recognizable and has certain defensive characteristics. This study systematically constructed an analytical framework for multi-scale collaborative defense mechanisms, revealing a collaborative defense model of “linear distribution–hierarchical defense–functional coordination”. This demonstrates the top–down strategic thinking of the ancient Chinese military system and provides a new perspective for the study and protection of linear military heritage corridors.